Toll-Like Receptor 8 Agonist Strengthens the Protective Efficacy of ESAT-6 Immunization to Mycobacterium tuberculosis Infection - Tang, Jun; Sun, Mengmeng; Shi, Guiying; Xu, Yanfeng; Han, Yunlin; Li, Xiang; Dong, Wei; Zhan, Lingjun; Qin, Chuan (Frontiers in Immunology, 2018)
Accumulating evidence suggests important functions for human Toll like receptor 8 in vivo in tuberculosis and autoimmune diseases. However, these studies are limited by the lack of specific agonists and by the fact that the homology of TLR8 in human and mice is not sufficient to rely on mouse models. In this study, we examined the role of human TLR8 in the disease progression of experimental Mycobacterium tuberculosis (Mtb) infection, as well as the benefits provided by a TLR8 agonist against Mtb challenge in a human TLR8 transgenic mouse. We found that the expression of human TLR8 in C57BL/6 mice permits higher bacilli load in tissues. A vaccine formulated with ESAT-6, aluminum hydroxide, and TLR8 agonist provided protection against Mtb challenge, with a high percentage of CD44hiCD62Lhi TCM. Using ovalbumin as a model antigen, we demonstrated that the activation of TLR8 enhanced the innate and adaptive immune response, and provided a sustained TCM formation and Th1 type humoral response, which were mainly mediated by type I IFN signaling. Further research is required to optimize the vaccine formulation and seek optimal combinations of different TLR agonists, such as TLR4, for better adjuvanticity in this animal model.